Impact of the Covid-19 pandemic on the maternal mortality rate in Brazil: trend and spatial distribution - Izabel Cristina da Silva Carvalho; Márcio Dênis Medeiros Mascarenhas; Malvina Thais Pacheco Rodrigues; Jesusmar Ximenes Andrade; Fernando Ferraz do Nascimento; Jardeliny Corrêa da Penha (Revista Gaúcha de Enfermagem, 2024)
ABSTRACT Objective: To analyze the impact of the Covid-19 pandemic on the Maternal Mortality Ratio in Brazil from 2018 to 2021. Method: Ecological time series study, which analyzed the trend and spatial distribution of maternal deaths from 2018 to 2021, with data obtained from the Mortality and Live Birth Information System. The Maternal Mortality Ratio values were subjected to Prais-Winsten linear regression analysis using Stata program, version 14.0. The evolution of the Maternal Mortality Ratio in the regions was presented on maps created using the TabWin software. Results: A total of 8,229 maternal deaths were recorded in the period. The year 2021 recorded the highest Maternal Mortality Ratio (113.1 maternal deaths per 100,000 live births). Brazil showed a stationary trend, while the North region had a higher Maternal Mortality Ratio across the four years, showing an increasing trend, along with the Northeast, while the Central-West, South and Southeast showed a stationary trend. Conclusion: Despite the stationary trend in most Brazilian regions, the Maternal Mortality Ratio increased, especially in 2020 and 2021, years of the Covid-19 pandemic, which demonstrates the need for constant monitoring of vulnerabilities among women during the pregnancy-puerperal cycle to prevent maternal deaths.